BRIGHTNESS REGULATOR BIT HIGH PRESSURE LAMPS FOR PLANTS OUTDOOR LIGHTING - , О. Ю., В. М., В. Ф. (Municipal economy of cities. Series: «Economy science», 2013)
The possibility of creating keruyemyh lighting installations based group controls the brightness of the high-pressure discharge lamps